2005
DOI: 10.1016/s1525-1578(10)60578-8
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Multiplexing, Polymerase Chain Reaction-Based Assay for the Analysis of Chromosome 18q Status in Colorectal Cancer

Abstract: Chromosome 18q allelic loss has been reported to have prognostic significance in stage II colorectal carcinoma. We have developed a fluorescent multiplex polymerase chain reaction assay to analyze five microsatellite markers (D18S55, D18S58, D18S61, D18S64, and D18S69) for allelic loss at the long arm of chromosome 18. Amplicon detection and evaluation was accomplished by capillary electrophoresis using an ABI 310 genetic analyzer. Robustness of the assay when performed on DNA extracted from formalinfixed, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Microsatellite analysis allows the detection of AI by comparing the intensities of the paternal and maternal alleles between normal and tumour tissues of heterozygous patients and then by calculating a quotient of the respective allele ratios between normal and tumour tissue. A standardized cut-off value for the determination of AI is not clearly defined and various studies used cut-off values in the range below 0.5–0.6 or above 1.5–2.0, which correspond to a reduction in the intensity of one of the alleles of at least 40–50% 8 , 9 , 18 21 . For our assay, we experimentally determined individual cut-off values for each microsatellite marker.…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellite analysis allows the detection of AI by comparing the intensities of the paternal and maternal alleles between normal and tumour tissues of heterozygous patients and then by calculating a quotient of the respective allele ratios between normal and tumour tissue. A standardized cut-off value for the determination of AI is not clearly defined and various studies used cut-off values in the range below 0.5–0.6 or above 1.5–2.0, which correspond to a reduction in the intensity of one of the alleles of at least 40–50% 8 , 9 , 18 21 . For our assay, we experimentally determined individual cut-off values for each microsatellite marker.…”
Section: Discussionmentioning
confidence: 99%
“…In several publications, the variability in STR identified by CE was demonstrated as being a significant diagnostic marker of cancer. Mathies' group developed a sensitive two-color labeling method with ET primers for the high-throughput STR-based screening of bladder cancer patients . Detection of a size difference in PCR amplicons from normal and tumor DNA is an indication of expansion or deletion in the microsatellites in the five different loci used as markers.…”
Section: 7 Cancermentioning
confidence: 99%
“…The frequency 18q LOH in our series overlaps with the majority of that reported in similar studies. 23 However, looking at single marker level, we found that the loss of D18S61 was paradoxically associated with more favorable prognosis in Stage II and III colon carcinoma. This evidence was especially significant for Stage II and untreated patients (Figs.…”
Section: Discussionmentioning
confidence: 77%